2017
DOI: 10.4236/oalib.1103598
|View full text |Cite
|
Sign up to set email alerts
|

An SIS Epidemic Model with Infective Medium and Feedback Mechanism on Scale-Free Networks

Abstract: In this paper, a modified SIS (susceptible-infected-susceptible) model with infective medium and feedback mechanism on scale-free networks is presented. The model is suited to describe some epidemic spreading which are not only transmitting by medium but also spreading between individuals by direct contacts. Considering biological relevance and people's subjective consciousness, we introduce medium and feedback to describe the epidemic spreading. By mathematical analysis, we obtain the epidemic threshold and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…That is, the threshold approaches zero in the limit of a large number of edges and nodes, and even a quite small infectious rate can produce a major epidemic outbreak. Liu XD et al [8] presented an SIS (susceptible-infected-susceptible) epidemic model with infective medium and feedback mechanism on scale-free networks. They found that the epidemic is not only spread between individuals by direct contacts but also transmitted by medium, people's initial response when epidemic disease outbreaks have been also considered.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the threshold approaches zero in the limit of a large number of edges and nodes, and even a quite small infectious rate can produce a major epidemic outbreak. Liu XD et al [8] presented an SIS (susceptible-infected-susceptible) epidemic model with infective medium and feedback mechanism on scale-free networks. They found that the epidemic is not only spread between individuals by direct contacts but also transmitted by medium, people's initial response when epidemic disease outbreaks have been also considered.…”
Section: Introductionmentioning
confidence: 99%